Medicinal plants and foods with metaphorical concepts in Rumi's "Masnavi Manavi": The psychosomatic approach to human health - Zahra Ekhtiari; Mousa-; Zahra Gholamnezhad (Mashhad University of Medical Sciences, 2023)
Objective: "Masnavi Manavi" is one of the most valuable texts of Persian literature. In this book, Rumi (Mevlana) with a unique method and in the form of moral stories teaches life lessons, mystical truths and even therapeutic advices to people. The aim of this study is to highlight the medicinal plants and foods that had been applied both in somatic and spiritual concept in "Masnavi Manavi' poems.Materials and Methods: For this purpose, a library-based, descriptive and analytical method was used.Results: Some medicinal plants and food terms such as rose-water, vinegar, honey, oxymel, common reed, grape, onion, garlic and wheat are mentioned in this study to show Rumi's metaphorical and therapeutic approach as a doctor who treats both soul and body. In fact, Rumi's intention to apply these terms was to express his ideas and views about the inseparability of physical and spiritual aspects in human health and well-being.Conclusion: Rumi focus in "Masnavi Manavi" moral stories is the soul health and consider body as carrier of the soul. Therefore, because of this psychosomatic approach to human disease, he selects the most suitable herbs and foods for explaining spiritual and somatic medicine.